Pengembangan Modul Berbasis Permainan Bahasa untuk Pembelajaran Kosa Kata Kelas I SDN Mojoroto 4 - Azizah Martha Kinanty; Rian Damariswara; Agus Budianto (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was motivated by the results of observations, interviews, and tests conducted with 1th students at SDN Mojoroto 4. On the observations, it was found the teacher relied solely on the school’s textbook as a learning resource and used a lecture-based teaching method. There was a lack of innovation in instructional delivery, which led to students having limited vocabulary mastery and difficulty in constructing words. Interviews with some students revealed that they quickly became bored with the monotonous learning process. Therefore, a language game-based module was needed to address these issues. The objectives of this study are: (1) To determine the validity of module, (2) To determine the practicality of the module, and (3) To determine the effectiveness of the module. The development model used was ADDIE, which includes the following stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The validity test results showed that the module expert gave a score of 92%, and the material expert gave a score of 80%. Practicality test results from teacher response questionnaires reached 94%, student responses in the limited trial reached 95%, and in the wider trial reached 92%. Effectiveness test results showed a classical percentage of 100% in both limited and wider trials. It can be concluded that the developed language game-based module is valid, practical, and effective.